Chinese Herbal Medicine Reduces the Risk of Heart Failure in Hypertensive Patients: A Nationwide, Retrospective, Cohort Study - Liu, Chun-Ting; Hung, I-Ling; Hsu, Chung Y.; Hu, Kai-Chieh; Chen, Yung-Hsiang; Tsai, Ming-Yen (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypertension (HTN) is the leading preventable risk factor for cardiovascular disease worldwide. Patients with HTN are at higher risk for heart failure (HF). The currently available therapeutic approaches for HTN do not always optimally control blood pressure or are not suitable for hypertensive patients who have a higher number of comorbidities. This study aimed to determine whether Chinese herbal medicine (CMH)-based interventions could reduce the risk of HF in hypertensive patients. Methods: This retrospective study randomly selected 2 million enrollees from the National Health Insurance Research Database and identified 507,608 patients who were newly diagnosed with HTN in 2000–2017. After 1:1 frequency-matching by age, sex, index year, income, urbanization, duration of HTN, comorbidities and antihypertensive medications, we selected 8,912 eligible patients in each group. During 16 years of follow-up, 380 CHM users and 426 CHM non-users developed HF, representing incidence rates of 6.29 and 7.43 per 1000 person-years, respectively. Results: CHM users had significantly lower HF risk compared with CHM non-users (adjusted HR = 0.85, 95% CI 0.74 to 0.98). The markedly predominant effect was observed in those receiving CHM products for more than 180 days (adjusted HR = 0.65). The frequently prescribed formula, Jia-Wei-Xiao-Yao-San, and the single herbs Ge Gen, Huang Qi, Du Zhong, Huang Qin, and Chuan Xiong were significantly associated with lower risk of HF. Conclusions: This population-based study revealed decreased HF risk in hypertensive patients with CHM use. These findings may provide a reference for HF prevention strategies and support the integration of CHM into clinical intervention programs that provide a favorable prognosis for hypertensive patients.